STRATEGI PENGEMBANGAN OBJEK WISATA PANTAI CAROLINA - Herman Aditya Nainggolan; Syafri Anwar (JURNAL BUANA, 2022)
This study aims to: 1. To determine the drivers and inhibitors of Carolina Coastal Tourism Objects. 2. to find out the strategy for developing the Carolina Coastal Tourism Object. This type of research is descriptive qualitative, SWOT analysis. The results of this study indicate that: 1. The driving factor which has a very high category is road access to tourist objects that is adequate and can be reached by public transportation with a mean of 4.90 (strength) and the number of carolina beach tourists who want to visit with a mean of 4.70 ( opportunities). Meanwhile, the inhibiting factors which have a very high category are budget constraints for the cost of facilities and infrastructure with a mean of 1.20 (weakness) and the awareness of tourists to protect tourist objects with a mean of 1.40 (threats). 2.Colina Coast Tourism Object Development Strategy, namely by increasing the promotion of carolina beach tourism objects, caring for things that are carolina beach selling values, repairing and completing facilities and infrastructure in carolina beach tourism objects, providing counseling in the form of knowledge. to the public regarding tourism so that all components can work together in efforts to develop Carolina Coastal tourism objects.